Monadic Theory of Order and Topology, II - Gurevich, Yuri (Israel Journal of Mathematics, 1979)
Assuming the Continuum Hypothesis, we interprete the theory of (the cardinal of) continuum with quantification over constructible (monadic, dyadic, etc.) predicates in the monadic (second-order) theory of real line, in the monadic theory of any other short non-modest chain, in the monadic topology of Cantor's Discontinuum and some other monadic theories. We exhibit monadic sentences defining the real line up to isomorphism under some set-theoretic assumptions. There are some other results.